A trianoni békeszerződés hatásai a királyi ítélőtáblákra - különös tekintettel a szegedire - Antal Tamás (2017)
The Peace Treaty concluded in Trianon (Versailles) on 4 Jun 1920, after the lost World War I, had dramatic effects not only on the economy and the territory of the Hungarian Realm but on the system of national courts as well. The present study aims to give a view to the problem with special regard to the appeal court of Szeged in the second decade of the 20th century. The author deals with the transformation of the geographic conditions and the new scope of jurisdictional authorities as well as the provisional budgetary and financial measures. According to the territorial modification Hungary lost six of eleven appeal courts, the remaining five ones were located in Budapest, Szeged, Debrecen, Pécs and Győr. The appeal court of Szeged had been one of the largest and busiest of all before the Great War, but after that the court in question became one of the smallest. Its presidents took serious efforts to increase the relevant territory but without any success in this period. The accommodation was not suitable either, the palace in which the court operated was not large enough for the comfortable work, while on the other hand its former elegant building was occupied by the university of Szeged for an undefined period of time. The post-war economic creases caused monetary difficulties for the justices, too, as their official salary was not enough to finance their living conditions although the salary of judges and public prosecutors had been insured by a special act in the stream of the political consolidation of 1920. The reputation of the jurisdictional organs was also suffered by the modified civil and criminal procedural acts, which did not protect the parties and the accused men’s interests so confidently than it had been the law and practice earlier. By these topics one can read further information on the history of the Hungarian jurisdiction and the legal professionals after World War I and before the global economic creases started in 1929/30.
Keywords: Társadalomtudományok; Jogtudomány